Explaining and Modeling Strategic Alignment with Environmental Performance and Green Innovation Approach in the Food Industry - Meshkinghalam, Leila; Rajabzadeh Ghatari, Ali; Pilehvari, Nazanin (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: To investigate the relationship between strategic alignment and environmental performance.Methodology: This study employed a descriptive-correlational research design. Data were collected from senior and middle managers of publicly traded companies in the food industry using adapted questionnaires. Hypotheses were tested using the partial least squares (PLS) method and analyzed through SPSS 23 and Smart PLS software.Findings: The results demonstrated that strategic alignment positively and significantly impacts green capacity, environmental strategy, green innovation, and green human resource management. Furthermore, green capacity, environmental strategy, green innovation, and green human resource management each positively and significantly influence environmental performance. The overall model fit was found to be excellent, with a calculated GOF value of 0.741.Conclusion: Strategic alignment plays a critical role in enhancing environmental performance by fostering green capacity, promoting innovative environmental practices, and integrating green strategies within organizational processes. This study provides a foundational framework for understanding how strategic alignment can be leveraged as a powerful tool for improving organizational sustainability and competitiveness.